2019
DOI: 10.1038/s41408-019-0196-6
|View full text |Cite
|
Sign up to set email alerts
|

Antibody–drug conjugate, GSK2857916, in relapsed/refractory multiple myeloma: an update on safety and efficacy from dose expansion phase I study

Abstract: Interim analyses of a phase I study with GSK2857916, an antibody–drug conjugate against B cell maturation antigen, have previously reported a 60% overall response and 7.9 months progression-free survival in relapsed/refractory multiple myeloma (MM). We provide updated safety and efficacy results of the BMA117159 trial following an additional 14 months' follow-up. This open-label, first-in-human, phase I study was conducted at nine centres in the USA, Canada and the UK, and included adults with MM and progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
193
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 191 publications
(197 citation statements)
references
References 23 publications
3
193
1
Order By: Relevance
“…A phase I trial investigating monotherapy with the antibody demonstrated a 38.5%% ORR and a median PFS of 6.2 months in those with disease refractory to daratumumab, a proteasome inhibitor and an immunomodulator. 49 Treatments Using Bispecific T-cell Engager Technology. Bispecific T-cell engagers (bispecifics) contain 2 single-chain variable fragments connected by a linker molecule.…”
Section: Joseph Mikhaelmentioning
confidence: 99%
“…A phase I trial investigating monotherapy with the antibody demonstrated a 38.5%% ORR and a median PFS of 6.2 months in those with disease refractory to daratumumab, a proteasome inhibitor and an immunomodulator. 49 Treatments Using Bispecific T-cell Engager Technology. Bispecific T-cell engagers (bispecifics) contain 2 single-chain variable fragments connected by a linker molecule.…”
Section: Joseph Mikhaelmentioning
confidence: 99%
“…Trudel and coworkers conducted the first-in-human phase 1 study with GSK2857916 monotherapy in heavily pre-treated RRMM (DREAMM-1, NCT02064387) [100,101]. In the initial 38 patients, the authors selected the optimal dose of GSK2857916 (3.4 mg/kg Q3 W as a 1-h infusion).…”
Section: Gsk2857916 (Belantamab Mafodotin)mentioning
confidence: 99%
“…In 2018, the results of a first in-human phase I study investigating GSK2857916, a BCMA-targeting mAb conjugated to the antimitotic agent monomethyl auristatin F (MMAF), in 73 RRMM patients were published. BCMA, a transmembrane receptor required for B cell maturation, was chosen as an optimal target, as it is expressed almost exclusively on MM cells and plasma cells [104][105][106]. In the dose-escalation phase of the study, 38 patients received escalating doses of IV GSK2857916 (0.03-4.6 mg/kg) every 3 weeks.…”
Section: Rationalementioning
confidence: 99%
“…The most common treatment-related toxicities were thrombocytopenia (63%; grades 3-4: 26%) and corneal events in terms of blurred vision and photophobia (51%; grades 3-4: 3%). Ocular toxicity was mainly limited to grades 1-2 and was reversible and easily manageable with dose reductions (51% of patients) [104,106]. Because GSK285791 showed high ORR in patients previously treated with anti-CD38 mAbs, a phase I/II clinical trial exploring its efficacy as monotherapy in patients with previous exposure to daratumumab/isatuximab has recently completed enrollment and results will soon be available (NCT03525678).…”
Section: Rationalementioning
confidence: 99%